Contribution of Shelterbelts in Employment Generation in Arid Zone of Western Rajasthan - Gajja, B L; Prasad, Rajendra; Mertia, R S; Samra, J S (Annals of Arid Zone, 2016)
An attempt has been made in this paper to document the impact of shelterbelt on net profit. The land allotment in IGNP was made on the basis of ‘murba’ (which is equivalent to 5 ha). The primary data were collected from 40 farmers with shelterbelt and 40 from non-shelterbelt farms selected randomly in each area of tube well and canal command area of IGNP Phase-II in Mohangarh. The labor decomposition model was used to define the contribution of shelterbelt in employment generation and also increase in complementary inputs. The new technology (shelterbelt) is supposed to increase economic activities by increasing productivity, efficiency and profitability. The results indicated that total additional employment generated by shelterbelt technology was 106.4%, of this 76.5% employment was generated by shelterbelt alone and remaining 29.9% by complementary inputs. Therefore, it is concluded that by adoption of shelterbelt technology employment opportunity can be increased. Key words: Adoption, complementary inputs, employments, shelterbelt